2020
DOI: 10.1093/eurpub/ckaa058
|View full text |Cite
|
Sign up to set email alerts
|

Use of amenable mortality indicators to evaluate the impact of financial crisis on health system performance in Greece

Abstract: Background Greece experienced the largest reduction in its health care budget of any European country during the economic crisis of 2008–15. Here, we test the hypothesis that budget reductions worsened health system performance in Greece, using the concept of Amenable Mortality to capture deaths which should not occur in the presence of effective and timely health care. Methods Amenable mortality was calculated from national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Although both all-cause and amenable mortality have decreased, amenable mortality shows a more pronounced decreasing trend. This pattern had already been described in a similar way in other studies in Europe [23,38,39]. In the Spanish case, this might suggest that the decrease could be due to preventive measures in risk factors and advances in treatments and health technology [6], as well as the entry into force of law 42/2010 on sanitary measures against smoking that regulates the sale, supply, consumption, and advertising of tobacco [34,40].…”
Section: Evolution Of the Risk Of Deathsupporting
confidence: 73%
See 1 more Smart Citation
“…Although both all-cause and amenable mortality have decreased, amenable mortality shows a more pronounced decreasing trend. This pattern had already been described in a similar way in other studies in Europe [23,38,39]. In the Spanish case, this might suggest that the decrease could be due to preventive measures in risk factors and advances in treatments and health technology [6], as well as the entry into force of law 42/2010 on sanitary measures against smoking that regulates the sale, supply, consumption, and advertising of tobacco [34,40].…”
Section: Evolution Of the Risk Of Deathsupporting
confidence: 73%
“…This reduction struck unevenly depending on the position of the people and social groups in the social structure and depending on geographical location (rural/urban, centre/peripheral, outskirts, etc.). Therefore, as amenable mortality depends directly on the response capacity of the health system, its use is not only relevant as an indicator of the crisis impact, but also as an indicator of the inequalities of that impact at different socioeconomic or educational levels, sex/gender, age, ethnic group, or geographical area; so reveal recent studies in Spain [6,22] and Europe [23].…”
Section: Introductionmentioning
confidence: 99%
“…Amenable mortality, or deaths from causes that should not occur in the presence of high-quality health care, 15 , 16 has been used as a measure of the health-care dimension of health system performance for nearly 50 years. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 The most widely used list of causes of mortality amenable to health care was developed by Nolte and McKee, and has since been used to compare high-income countries' performances at length. 10 , 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 A recent study by Kruk and colleagues 34 used case-fatality rates for causes included in the McKee and Nolte list and additional diseases to estimate the separate effects of utilisation versus quality for 137 countries.…”
Section: Introductionmentioning
confidence: 99%
“…In the short term, some studies found an association with premature mortality, 41 suicide, 42 homicide 43 and death amenable to health care. 44 The impact of the recession on the population's health is not yet fully clear, as socio-economic consequences of the recession are still developing. 45 This is in keeping with recent international studies identifying long-term effects on health inequalities, 46 mortality, 47 child mortality 48 and life expectancy.…”
Section: Discussionmentioning
confidence: 99%